Influence of immigration on dynamics of economic growth and on condition and standing of public finance of Spain - Romiszewska, Anna (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
At the turn of 20th and 21st century, Spain was one of target countries of earning immigration not only in the European Union, but in the entire world as well. This paper aims at analyzing the influence of immigration on the dynamics of Spanish GDP in the context of its direct influence on the level of productivity, employment rate, as well as the demographic factor that results from the share of working foreigners in the creation of national income, and the indirect impact resulting from its influence on, among other things, functioning of the labor market through mobility or occupational activity, as well as on changes in the volume of demand notified in the economy. Next, we are going to present the influence of immigration on condition and standing of public finance against the background of revenues generated by foreigners and public expenditures borne on immigrated population. Due to the size of this paper and difficult availability of data, the analysis will cover the country as a whole, disregarding regional differences